Time-motion characteristics, notational analysis and physiological demands of tennis match play: a review - Kilit, B.; Arslan, E.; Soylu, Y. (Acta Kinesiologica, 2018)
Tennis is a sport characterized by a combination of physical actionssuch as running at different speeds, acceleration, turns, strokes and game-specific actions. In this regard, competitive tennis players require not only well-developed aerobic endurance and anaerobic capacity, but also technical and tactical skills to achieve high levels of performance during training and matches. The aim of this review was toinvestigate the demands of competitive tennis match play in terms of physiological responses, time-motion characteristics and match analysis. Three sport science journal databases PubMed, ISI Web of Knowledgeand SPORTDiscus were screened for papers published until May 2018. The following keywords were used in various combinations with tennis: "notational analysis", "physiological demands", "simulated match", "time-motion", and "match characteristic". In this review, studies had to meet follow inclusion criteria: cross sectional or longitudinal design, case control studies, or experimental studies electronically published in English. All studies demonstrated high methodological quality. This review presents a useful synthesis of all research into match performance in tennis, including the investigation of the internal and external load of the tennis match play and helps to guide for future research.